Inovasi Teknologi Pembakaran Sampah Minim Asap (INSEMA) sebagai Upaya Mitigasi Dampak Lingkungan dan Bencana Kesehatan di Desa Gandasoli, Kecamatan Cikakak - Aritonang, Jecky Evanglis; Khawarizmi, Khawarizmi; Aziz, Fahri; Rizaldi, Rizaldi; Supriatna, Reval; Azmi, Zahran Nurul; Tsany, Reihan Safari; Haerunnisa, R Alya; Salsabila, Salsabila; Angelivia, Rizky; Ramli, Muhamad; Parida, Ega Ngadi; Jamilah, Neng Bernanda; Pratama, Rivaldi Fauzi; Temorubun, Kristomus (PT. Amirul Bangun Bangsa, 2025)
The Community Service Program (KKN) in Gandasoli Village, Cikakak Subdistrict, began with field observations to identify priority issues faced by the community. The observations revealed that the main problem was waste management, particularly the practice of open burning, which produced thick smoke, polluted the air, and posed health risks. As a solution, the CSL students developed an innovation in the form of a low-smoke waste incineration technology (Insema) using used oil drums as simple incinerators. This program was designed, implemented, and evaluated independently by the CSL students based on the results of their field observations. The results of the experiment showed that this low-smoke incinerator could reduce thick smoke compared to conventional waste incineration. This work program demonstrates the potential of appropriate technology in supporting more environmentally friendly waste management, reducing health risks to the community, and providing sustainable alternative solutions that can be applied in rural areas